2021
DOI: 10.1002/cjoc.202100167
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Highly Efficient Photocatalyst with Core‐Shell Au@Ag/C@SiO2 Hybrid Structure towards Visible‐Light‐Driven Photocatalytic Reduction

Abstract: Main observation and conclusion Herein, we report a rational construction of Au@Ag/C@SiO2 system with Au@Ag core‐shell nanoparticles (NPs) as a promising photocatalyst based on the plasmonic coupling effect for the first time towards the photoreduction of nitroaromatic compounds under visible light. The combination and elaborate construction of Au@Ag NPs, carbon microspheres and mesoporous SiO2 shell can endow this system with several outstanding features towards photocatalytic reaction. Firstly, the broadband… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 46 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…In recent years, photocatalysis has received widespread attention due to its green and renewable advantages. [50] Shi et al conducted a study on the photocatalytic conversion of FF using ultrathin SnNb 2 O 6 nanosheets loaded with Pt. [51] Their research revealed that nanosheets, with a mere 4.1 nm thickness, demonstrated exceptional proficiency in separating light-generated carriers.…”
Section: Pt-based Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, photocatalysis has received widespread attention due to its green and renewable advantages. [50] Shi et al conducted a study on the photocatalytic conversion of FF using ultrathin SnNb 2 O 6 nanosheets loaded with Pt. [51] Their research revealed that nanosheets, with a mere 4.1 nm thickness, demonstrated exceptional proficiency in separating light-generated carriers.…”
Section: Pt-based Catalystsmentioning
confidence: 99%
“…Changes in activity are brought about by the presence of Sn, which enhances the polarization and adsorption of the carbonyl bond, resulting in great selectivity to the unsaturated alcohols. In recent years, photocatalysis has received widespread attention due to its green and renewable advantages [50] . Shi et al.…”
Section: Conversion Of Ff To Renewable Value‐added Chemicalsmentioning
confidence: 99%
“…Recently, plasmonic photocatalysis based on the nanoparticles (NPs) of plasmonic metals (Au, Ag, Cu, etc.) has attracted extensive attention due to the efficient harvesting of sunlight across the entire visible spectrum via the surface plasmon resonance (SPR) effect, which provides an efficient strategy to remarkably enhance the efficiency of solar energy conversion. , The energetic (hot) electrons are generated in plasmonic nanocatalysts through the SPR process, which can facilitate the chemical reactions. Meanwhile, developing advanced hybrid photocatalysts composed of plasmonic metal and semiconductor has been a forefront topic for photo-driven water splitting to produce hydrogen. , For the hybrid plasmonic photocatalyst, it not only retains the inherent optical properties of plasmonic metal and semiconductor but also integrates the multiple functions through synergetic coupling between plasmonic resonances and excitonic transitions . It is reported that the photon energy harnessed by a plasmonic metal is delivered to the adjacent semiconductor via either an SPR-induced hot electron transfer route or electromagnetic field-mediated plasmon energy transfer process. Moreover, the interface engineering between a plasmonic metal and semiconductor provides an effective approach to efficiently modulate the plasmon-exciton coupling since the transfer of hot electrons from plasmonic metal to semiconductor must proceed across its interface. , Therefore, developing an efficient strategy to properly engineer the interface is of paramount significance for efficient maneuvering of hot electrons, including the construction of hybrid core–shell architecture.…”
Section: Introductionmentioning
confidence: 99%
“…has attracted extensive attention due to the efficient harvesting of sunlight across the entire visible spectrum via the surface plasmon resonance (SPR) effect, which provides an efficient strategy to remarkably enhance the efficiency of solar energy conversion. 13,14 The energetic (hot) electrons are generated in plasmonic nanocatalysts through the SPR process, which can facilitate the chemical reactions. 15−17 Meanwhile, developing advanced hybrid photocatalysts composed of plasmonic metal and semiconductor has been a forefront topic for photo-driven water splitting to produce hydrogen.…”
Section: Introductionmentioning
confidence: 99%